2009
DOI: 10.1016/j.devcel.2009.04.016
|View full text |Cite
|
Sign up to set email alerts
|

The Retromer Coat Complex Coordinates Endosomal Sorting and Dynein-Mediated Transport, with Carrier Recognition by the trans-Golgi Network

Abstract: SummaryEarly endosome-to-trans-Golgi network (TGN) transport is organized by the retromer complex. Consisting of cargo-selective and membrane-bound subcomplexes, retromer coordinates sorting with membrane deformation and carrier formation. Here, we describe four mammalian retromers whose membrane-bound subcomplexes contain specific combinations of the sorting nexins (SNX), SNX1, SNX2, SNX5, and SNX6. We establish that retromer requires a dynamic spatial organization of the endosomal network, which is regulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
291
1
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 268 publications
(317 citation statements)
references
References 61 publications
22
291
1
3
Order By: Relevance
“…Consistent with our findings, they discovered that SNX6 associates with p150 Glued and that SNX6 interacts with SNX1/2 [40]. They also demonstrated that suppression of p150 Glued redistributes the retromer-labeled endosomes from regions surrounding the TGN to a more peripheral location [40]. In our study, to investigate the role of adaptor protein-mediated motor-cargo interaction, we overexpressed the N-terminus of p150 Glued as a dominant-negative mutant to compete with endogenous WT protein for dynein, and found that this mutant, which lacks the SNX6 interaction site, causes failure in formation, stabilization and exit of retromer-associated transport intermediates from endosomes, therefore blocking CI-MPR retrieval (Figure 8 and Supplementary information, Movies S3-S5).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Consistent with our findings, they discovered that SNX6 associates with p150 Glued and that SNX6 interacts with SNX1/2 [40]. They also demonstrated that suppression of p150 Glued redistributes the retromer-labeled endosomes from regions surrounding the TGN to a more peripheral location [40]. In our study, to investigate the role of adaptor protein-mediated motor-cargo interaction, we overexpressed the N-terminus of p150 Glued as a dominant-negative mutant to compete with endogenous WT protein for dynein, and found that this mutant, which lacks the SNX6 interaction site, causes failure in formation, stabilization and exit of retromer-associated transport intermediates from endosomes, therefore blocking CI-MPR retrieval (Figure 8 and Supplementary information, Movies S3-S5).…”
Section: Discussionsupporting
confidence: 80%
“…While this paper was in preparation, the SNX6-p150 Glued interaction was reported by Peter J Cullen's group [40]. Consistent with our findings, they discovered that SNX6 associates with p150 Glued and that SNX6 interacts with SNX1/2 [40].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Furthermore, we sought to determine whether toca-1(tm2056); toca-2 (ng11) double mutant, or RNAi-mediated depletion of cdc-42 or par-6 by RNAi, effects on ALM polarity are enhanced by retromer mutant vps-29(tm1320). Previous work showed that the Wnt phenotype of vps-29(tm1320) is much weaker than that of vps-26 or vps-35 mutants but shows enhanced phenotypes when combined with mutations in known Wnt-pathway components or retrograde recycling regulators (13,(48)(49)(50). Consistent with published work, we observed only normal ALM polarity in vps-29 (tm1320) single mutants (47).…”
Section: Loss Ofsupporting
confidence: 82%
“…The retromer is a multiprotein complex, conserved among eukaryotes, that is involved in the recycling of transmembrane receptors and retrograde transport of cargo proteins from endosomes to the trans-Golgi network (13). In mammals, the retromer consists of two distinct subcomplexes: one composed of a dimer of Sorting Nexins (SNXs) and the other, known as the core retromer, consisting of a trimer of vacuolar protein sorting (VPS) 26, VPS29, and VPS35 proteins (13,14). The Arabidopsis genome contains genes encoding all components of the retromer complex, including three SNX genesdesignated SNX1, SNX2a, and SNX2b-three genes coding for VPS35 isoforms (VPS35a, VPS35b, and VPS35c), two genes encoding VPS26 isoforms (VPS26a and VPS26b), and a single gene encoding VPS29 (12,(15)(16)(17).…”
mentioning
confidence: 99%